Caregiver Responses to Child Posttraumatic Distress: A Qualitative Study in a High‐Risk Context in South Africa. Issue 5 (27th October 2017) - Williamson, Victoria; Butler, Ian; Tomlinson, Mark; Skeen, Sarah; Christie, Hope; Stewart, Jackie; Halligan, Sarah L
Abstract: Many low‐ and middle‐income countries (LMIC) have high rates of child trauma exposure and limited access to psychological services. Caregivers are often a child's key source of support following trauma in such contexts. The aim of this study was to explore the experiences of primary caregivers in supporting their child posttrauma. Qualitative interviews were conducted with 20 female caregivers from a high‐risk settlement in Cape Town following child trauma exposure. Children were exposed to significant traumatic events, including gang violence, assault, and fatalities of close relatives. The data were analyzed using thematic analysis; several key themes emerged. First, caregivers were typically aware of child distress posttrauma, based primarily on manifest behaviors. Second, caregivers identified varied ways of providing support, including being warm and responsive; seeking to ensure physical safety by encouraging the child's perceptions of the community as dangerous; and encouraging forgetting as a way of coping, with limited discussions of the event. Third, many barriers existed to accessing psychological treatment, and caregivers had low involvement in any interventions. Finally, caregivers also experienced significant distress that could impact their responses to their child. The results illustrate the challenges faced by caregivers in supporting children following trauma in LMIC contexts and the need for accessible psychological interventions.